Problem Penemuan Kebenaran dalam Putusan Mahkamah Konstitusi - Wibowo, Mardian (Jurnal Konstitusi, 2016)
Every effort of discovering the truth always faced with the possibility to slip. This possibility of slips also occurs in the Constitutional Court Decisions, specifically one which strongly related to material truth, such as in the decision related in dispute  of local general election result. Based on that certainty, this paper  attempts  to study the problems that could arise whenever the Constitutional Court manage to discover the truth, while also tries to present alternatives in the attempt to repair the aforemention slips.